Safeguarding Taiwan’s Sovereignty and Advancing Economic Relations with China: A Japanese Perspective - Adedotun Jamiu Saka; Taofeek Opeyemi Olaiya (Covenant University Journal of Politics and International Affairs, 2024)
The recent Taiwan and China conflict can be traced back to 1949 after the end of the civil war between the People’s Republic of China (PRC) and the Republic of China (ROC); the PRC won the civil war, and they took over the Mainland China and the ROC retreated to Taiwan and maintain the control of Taiwan till date. The PRC wants a unified China, and the ROC wants an independent Taiwan, which has increased tension in Asia. Japan has official relations with the PRC and unofficial relations with the ROC. PRC is the biggest Japanese trade partner, and a full-blown PRC and ROC conflict will affect the bilateral trade between the PRC and Japan; hence, this paper focuses on how Japan can prevent the Chinese takeover of Taiwan and increase its economic ties with China. The paper adopted a qualitative research method; secondary data and thematic analysis were used to analyze the study’s objectives. The study proposed policy recommendations on how Japan can prevent the PRC from taking over ROC and how Japan can improve economic ties with the PRC amid the conflict. Some of the proposed recommendations of the study are that Japan should broker a peace and conflict resolution between China and Taiwan, Japan should review Article 9 of her constitution, a tripartite ministry of trade that involves China, Taiwan, and Japan should be proposed, and a prior agreement on the status and management of each waterway or straits for economic purpose.